Parametric optimization in wire EDM of D2 tool steel using Taguchi method. (2021) - Sharma, Sahil; Kumar Vates, Umesh; Bansal, Amit
Abstract: Wire EDM is a non-traditional machining method which is widely used for machining of extremely hard material, and complex shapes which would not be possible using conventional machining methods. This method of machining is widely practised in mould, tool and die industries. In this process, there is no direct contact between the work piece material and wire electrode; therefore the hardness of work piece material is not a bounding factor for the machining process. In this process, removal of material to be done by producing a spark between the work piece material and the wire electrode. In the present work, the machining of AISI D2 die steel of 13 mm diameter was performed using a 0.25 mm dia wire electrode. The influence of various input process parameters (Ton, Toff, Ip, Tw) on the response characteristics (MRR, Ig, MT) was investigated by using Taguchi L9 orthogonal array. Signal to noise ratio and ANOVA will also employed in the study of response parameters.